A Matter of Life or Death: Productively Infected and Bystander CD4 T Cells in Early HIV Infection - Dechao Cao; Dechao Cao; Sushant Khanal; Sushant Khanal; Ling Wang; Ling Wang; Zhengke Li; Juan Zhao; Juan Zhao; Lam Nhat Nguyen; Lam Nhat Nguyen; Lam Ngoc Thao Nguyen; et al. (Frontiers in Immunology, 2021)
CD4 T cell death or survival following initial HIV infection is crucial for the development of viral reservoirs and latent infection, making its evaluation critical in devising strategies for HIV cure. Here we infected primary CD4 T cells with a wild-type HIV-1 and investigated the death and survival mechanisms in productively infected and bystander cells during early HIV infection. We found that HIV-infected cells exhibited increased programmed cell death, such as apoptosis, pyroptosis, and ferroptosis, than uninfected cells. However, productively infected (p24+) cells and bystander (p24-) cells displayed different patterns of cell death due to differential expression of pro-/anti-apoptotic proteins and signaling molecules. Cell death was triggered by an aberrant DNA damage response (DDR), as evidenced by increases in γH2AX levels, which inversely correlated with telomere length and telomerase levels during HIV infection. Mechanistically, HIV-infected cells exhibited a gradual shortening of telomeres following infection. Notably, p24+ cells had longer telomeres compared to p24- cells, and telomere length positively correlated with the telomerase, pAKT, and pATM expressions in HIV-infected CD4 T cells. Importantly, blockade of viral entry attenuated the HIV-induced inhibition of telomerase, pAKT, and pATM as well as the associated telomere erosion and cell death. Moreover, ATM inhibition promoted survival of HIV-infected CD4 T cells, especially p24+ cells, and rescued telomerase and AKT activities by inhibiting cell activation, HIV infection, and DDR. These results indicate that productively infected and bystander CD4 T cells employ different mechanisms for their survival and death, suggesting a possible pro-survival, pro-reservoir mechanism during early HIV infection.